Automated Pump Placement Algorithms for Optimal Sewer Network Design in Areas with Complex Terrain - Ralf Habermehl; Amin E. Bakhshipour; Timo C. Dilly; Ali Haghighi; Ulrich Dittmer (Engineering Proceedings)
We present a set of algorithms for automatically determining the best locations for lift stations and pressurized pipes in sewer networks. These algorithms are integrated into an optimization framework for automatic sewer network planning. The algorithms are developed based on graph theory and metaheuristic optimization to optimize the allocation of lift stations and pressure pipes. The proposed algorithms are applied to a real large-scale test case in Paranatinga, Brazil, and the results are compared with an existing design. This comparison highlights the algorithms’ effectiveness in designing cost-efficient sewer networks in areas with complex terrain.